DEVELOPMENT OF PLAGIARISM DETECTION APPLICATION ON THE TEXT DOCUMENTS USING RABIN-KARP ALGORITHM - Kadek Versi Yana (Universitas Pendidikan Ganesha, 2012)
This study was aimed to design and implement a plagiarism detection application on the Indonesian documents texts using Rabin-Karp algorithm. The input of this application such documents which have text file (*. txt, *. html, *. php, *. xml, *. doc, *. docx, *. rtf) and the output of this application is the percentage of similarity of two documents. The result of this study is an application which is called